AgNP and rhEGF-incorporating synergistic polyurethane foam as a dressing material for scar-free healing of diabetic wounds. Issue 23 (28th February 2017) - Choi, Hyun Jun; Thambi, Thavasyappan; Yang, Yool Hee; Bang, Sa Ik; Kim, Bong Sup; Pyun, Do Gi; Lee, Doo Sung
Abstract : Synergistic polyurethane foams comprised of AgNPs and rhEGF (AgNP/rhEGF-PUFs) were developed to treat diabetic wounds, which exhibited complete wound closure. Abstract : Diabetic wounds are a major health concern in diabetic wound care management. Various factors influence the biological phases of diabetic wound healing, causing improper wound healing. To surmount the issues associated with diabetic wounds, designing dressing materials with antibacterial and re-epithelization properties has the potential to promote successful wound healing. Here we prepared synergistic dressing materials by incorporating silver nanoparticles (AgNP) and recombinant human epidermal growth factor (rhEGF) into polyurethane foams (PUFs) and tested these materials in an animal model of diabetic full-thickness wounds. The AgNP/rhEGF-PUFs dressings exhibited excellent absorbency, fluid retention, and fluid handling properties. The hydrophilic surface of the PUF dressing could potentially enhance its antibacterial properties against pathogenic bacteria. In vitro cytotoxicity tests demonstrated that the PUFs are cytocompatible, and the AgNP/rhEGF-PUFs significantly enhanced the growth of L-929 cells. More importantly, examination of in vivo wound healing in a full-thickness balb/c mice model demonstrated that the AgNP/rhEGF-PUFs could significantly accelerate the healing of diabetic wounds. Furthermore, histological examination demonstrated that the AgNP/rhEGF-PUF dressings successfully reconstructed the impaired epidermis, as demonstrated by proper re-epithelization and collagen deposition. The wounds treated with the AgNP/rhEGF-PUFs dressings were completely closed by day 20, while wounds treated with AgNP-PUFs and gauze only closed 87 ± 2.30 and 64 ± 4.76%, respectively. These results demonstrated that our synergistic AgNP/rhEGF-PUFs comprise a successful fusion of antibacterial and re-epithelization agents, with promising future applications in diabetic wound healing.